Recent Progress on the Hydrodeoxygenation of Lignin-Derived Pyrolysis Oil Using Ru-Based Catalysts - Kim, Hyungjoo; Park, Jae Hyun; Ha, Jeong-Myeong; Kim, Do Heui (한국화학공학회, 2024)
Hydrodeoxygenation (HDO) of lignin-derived pyrolysis oil has received significant attention as a potential technology for replacing conventional petroleum-based fuels and chemicals. Ru-based HDO catalysts are in the limelight as HDO catalysts since they exhibit excellent catalytic activity while being cost-effective compared to other noble metal-based catalysts. Various studies have reported Ru-based catalysts used in the HDO of lignin-derived pyrolysis oil and its model compounds, and a variety of strategies have been utilized to tune the catalytic properties to enhance the performance and advance the understanding of the HDO reaction. This review discusses the recent publications on Ru-based catalysts used in the HDO of lignin-derived pyrolysis oil and its model compounds. Additionally, an overview of HDO reactions and the characteristics of HDO catalysts were summarized, and the general advantages of Ru catalysts, which are extensively used as attractive catalysts in the various reactions, are introduced. Various factors, including reaction conditions, support materials, and promoters, that can affect the performance of Ru-based HDO catalysts are organized, and the strategies utilized to modify the properties of the catalysts are categorized. Finally, the areas that require further development such that Ru-based HDO catalysts can overcome the remaining challenges are outlined.